2020
DOI: 10.2147/jmdh.s267732
|View full text |Cite
|
Sign up to set email alerts
|

<p>Stimulating Students’ Interprofessional Teamwork Skills Through Community-Based Education: A Mixed Methods Evaluation</p>

Abstract: Background: Interprofessional education (IPE) is suggested as a good means to prepare future healthcare professionals for collaborative work in interprofessional teams enabling them to solve complex health problems. Previous studies have advocated experiential IPE, including community-based IPE (CBIPE). This study aims to evaluate a CBIPE programme by exploring the students' perception toward CBIPE design and toward groups' teamwork. Methods: To identify students' perceptions of teamwork, the Interprofessional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 64 publications
(91 reference statements)
1
9
1
Order By: Relevance
“…Nursing students’ collaboration with other healthcare professionals and the community was rated high with a mean score of 4.16 ± 0.42. These results contradict existing literature where nursing students reported being insecure in collaborating with medical students, lacked confidence and understanding of team work (Lestari, Scherpbier & Stalmeijer 2020 :1143; Oxelmark et al 2017 :14). Considering that nurses work as part of a team, there is need to help student develop collaboration skills (Oldland et al 2020 :151).…”
Section: Discussion Of the Resultscontrasting
confidence: 85%
See 1 more Smart Citation
“…Nursing students’ collaboration with other healthcare professionals and the community was rated high with a mean score of 4.16 ± 0.42. These results contradict existing literature where nursing students reported being insecure in collaborating with medical students, lacked confidence and understanding of team work (Lestari, Scherpbier & Stalmeijer 2020 :1143; Oxelmark et al 2017 :14). Considering that nurses work as part of a team, there is need to help student develop collaboration skills (Oldland et al 2020 :151).…”
Section: Discussion Of the Resultscontrasting
confidence: 85%
“…Considering that nurses work as part of a team, there is need to help student develop collaboration skills (Oldland et al 2020 :151). There is evidence that some interventions can work to improve collaboration skills amongst healthcare students including nurses (Lestari et al 2020 :1143; Oxelmark et al 2017 :14).…”
Section: Discussion Of the Resultsmentioning
confidence: 99%
“…Similar to other studies, the results of the present systematic review showed that community-based education improved teamwork skills in nursing students [24,25,27,29,30]. Nursing students considered this training program to be successful, and felt that it enhanced their group activities and teamwork skills.…”
Section: Discussionsupporting
confidence: 87%
“…1. Seventeen articles published during 2004-2020 were included: including five quasi-experimental studies, three descriptive studies, four mixed method studies, and five qualitative studies [11,12,[19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]. The total number of participants was 1,866, ranging from 14 to 613 in each study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation